Computational fluid dynamics-based evaluation and optimisation of feed spacer design parameters for reverse osmosis membrane modules - Kavianipour, Omid (Curtin University, 2023)
This thesis provides insights into the impact of changing parameters on feed spacer performance, to look for possible trends and correlations, and to explain the observed patterns, in order to enhance the understanding of feed spacers in RO modules. Studies showed that selecting the best-performing spacer is not only related to the performance measure selected for comparison but is also affected by other operational parameters (flowrate and the concentration of salt in the feed).